Recurrent Appendicitis in Children: The Impact of a Poorly Known Disease - Monteiro, Sara (2023)
Chronic and recurrent appendicitis is rare in pediatric patients and can be easily misdiagnosed due to its unusual presentation and low incidence rate. We present the case of an 11-year-old male with recurrent right lower quadrant (RLQ) pain persisting for 19 months. The patient experienced pain flare-ups accompanied by paleness and gait limp, without fever or other symptoms. Despite extensive medical examinations, including imaging and endoscopy, a definitive diagnosis remained elusive. As serial abdominal ultrasounds reported an appendix at the upper limit of the normal caliber and symptoms persisted despite medical therapy, a diagnostic laparoscopy was performed, revealing a congested ileocecal appendix with erosions and granulocytic inflammatory infiltrate, consistent with appendicitis. Post-appendectomy, the patient's symptoms resolved, significantly improving his quality of life (QoL), as evidenced by the DISABKIDS Chronic Generic Module (DCGM). This case underscores the challenges in diagnosing chronic and recurrent appendicitis, emphasizing the need for improved awareness, case definitions, and research to better understand and manage these conditions. Moreover, the report highlights the substantial impact of such conditions on patients' physical, social, and psychological well-being using the only health-related QoL instrument developed across cultures for children with chronic diseases: the DCGM.